In Vitro Light‐Up Visualization of a Subunit‐Specific Enzyme by an AIE Probe via Restriction of Single Molecular Motion. Issue 25 (19th February 2020) - Zang, Tienan; Xie, Yachen; Su, Sa; Liu, Feiran; Chen, Qianqian; Jing, Jing; Zhang, Rubo; Niu, Guangle; Zhang, Xiaoling
Abstract: Enzymes contain several subunits to maintain different biological functions. However, it remains a great challenge for specific discrimination of one subunit over another. Toward this end, the fluorescent probe TPEMA is now presented for highly specific detection of the B subunit of cytosolic creatine (CK) kinase isoenzyme (CK‐B). Owing to its aggregation‐induced emission property, TPEMA shows highly boosted emission toward CK‐B with a fast response time and very low interference from other analytes, including the M subunit of CK (CK‐M). With the aid of a Job plot assay, ITC assay and molecular dynamics simulation, it was directly confirmed that the remarkably enhanced fluorescence of TPEMA in the presence of CK‐B results from the restriction of single molecular motion in the cavity. Selective wash‐free fluorescence imaging of CK‐B in macrophages under different treatments was successfully demonstrated. Abstract : The fluorescent probe TPEMA with aggregation‐induced emission is presented. It is used for in vitro specific discrimination of the B subunit of cytosolic creatine kinase isoenzyme in live cells by restriction of single molecular motion.